Making suggestions: A contrastive study of young Hong Kong and Australian students - Li, Eden Sum-hung (Journal of pragmatics, 2010)
This study contrasts the syntactic forms and pragmatic strategies adopted by Cantonese students in making suggestions in English (their L2) not only with Australian students, who serve as a target-based control group, but also with other Cantonese students in Cantonese (their L1), who serve to foreground the result of the above-mentioned comparison. In terms of syntactic forms, the study finds that in comparison with Australian students, Cantonese students in their L2 adopt fewer syntactic types in making suggestions. In addition, their suggestions are less likely to be embedded in elliptical or complex sentences but more likely to be preceded by textual themes and interpersonal metaphors. In terms of pragmatic strategies, Cantonese students resemble Australian students in their choices of perspective, directness and politeness in general. However, they show significant differences in their choices of suggestion strategies and redressive actions. Some of these differences resemble the preferential difference between the two languages while some reflect the subjects’ language competence. These observations call for further research and changes in the language classroom as well as language materials.